A novel vanadium/cobalt redox couple in aqueous acidic solution for redox flow batteries - Kocyigit, Nilufer; Gencten, Metin; Sahin, Mutlu; Sahin, Yucel (WILEY, 2020)
In this work, a novel aqueous electrolyte system consisting of cobalt and vanadium for redox flow battery was prepared to increase the cell voltage of the system for the first time in the literature. Electrolyte systems were characterized by using of cyclic voltammetry, differential pulse voltammetry, and electrochemical impedance spectroscopy to determine the effects of sulfuric acid and active ion concentration on the performance of the battery. Optimum sulfuric acid concentration was determined as 4.0 M for anolyte and catholyte. The effect of diffusion on mass transfer mechanism was higher than that of adsorption in each electrolyte of the flow battery system. Cyclic charge-discharge tests were carried out for the prepared novel electrolyte system. Discharge capacities of the electrolyte were determined as 430.1, 417.4, and 428.7 mAh for first cycle, second cycle, and third cycle, respectively. The cell potential of the redox flow battery in the electrolyte system during the charging process increased to 2.35 V which was also relatively higher than those of aqueous vanadium redox flow battery and aqueous iron flow battery. Obtained redox flow battery composition with its high cell potential can bring a new approach for the different application areas in the electrochemical energy storage.
Keywords: cobalt; vanadium; cyclic charge-discharge; cyclic voltammetry redox flow battery; PENCIL GRAPHITE-ELECTRODES; POSITIVE ELECTROLYTE; ALL-VANADIUM; ONE-STEP; ENERGY; PRECIPITATION; CHALLENGES; SULFATE; Energy & Fuels; Nuclear Science & Technology